The world of fatwas, or, The shariah in action - Shourie, Arun. (New Delhi : HarperCollins Publishers, 2012)
Study of Islamic canonical decisions (Fatwas) issued in India during the last hundred years.
Includes bibliographical references and index.
Refugee Studies Unit (RSU), CPJ
Keywords: Islam -- Controversial literature; Islam -- India -- Miscellanea